Does negative news reporting on the economy get reflected in companies' business situation? - David Iselin (ETH Zurich, KOF Swiss Economic Institute, 2015)
We examine the effects of negative news reporting on companies' self-assessment of their business situation. We compare survey data in the manufacturing sector in Switzerland with thousands of newspaper articles which we scan for particular keywords. Simple OLS regressions do not show a significant influence of news reporting on the self-assessment of the surveyed companies. However, the fact that our news data are available on a higher frequency permits us to examine if a MIDAS approach (regressing the daily news data on the monthly survey data) leads to any gain in information. Our results show influence of particular days which could give an early hint how companies see their business environment before the actual survey results are available.
Keywords: 330; Media Data; News; Uncertainty; Business Situation; Mixed Frequency Data; MIDAS